1987
DOI: 10.1152/jappl.1987.63.2.492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol on tissue glycogen metabolism in exercised oophorectomized rats

Abstract: The effect of both physiological and pharmacological doses of estradiol on exercise performance and tissue glycogen utilization was determined in oophorectomized estradiol-replaced (ER) rats. Doses of beta-estradiol 3-benzoate (0.02, 0.04, 0.1, 0.2, 1, 2, 4, or 10 micrograms.0.1 ml of sunflower oil-1.100 g body wt-1) were injected 5 days/wk for 4 wk. Controls were sham injected (SI). After treatment, the animals were run to exhaustion on a motorized treadmill. ER animals receiving the 0.02-microgram dose ran s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 0 publications
3
76
1
Order By: Relevance
“…The dose of estrogen selected in the present investigation was based on previous work done with physiological estrogen supplementation in the rat model. 10 Efficacy of hormone treatment was verified by plasma estradiol measurement with the use of the Bayer Centaur Automated Chemiluminescence System performed by the London Health Sciences Center, Division of Endocrinology. All animals demonstrated circulating estrogen levels within normative values for female rats (meanϮSD values are as follows: male rats, 10Ϯ6 pg/mL; intact female rats, 57Ϯ11 pg/mL; placebo-treated ovariectomized female rats, 13Ϯ8 pg/mL; and estrogen-treated ovariectomized female rats, 103Ϯ21 pg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…The dose of estrogen selected in the present investigation was based on previous work done with physiological estrogen supplementation in the rat model. 10 Efficacy of hormone treatment was verified by plasma estradiol measurement with the use of the Bayer Centaur Automated Chemiluminescence System performed by the London Health Sciences Center, Division of Endocrinology. All animals demonstrated circulating estrogen levels within normative values for female rats (meanϮSD values are as follows: male rats, 10Ϯ6 pg/mL; intact female rats, 57Ϯ11 pg/mL; placebo-treated ovariectomized female rats, 13Ϯ8 pg/mL; and estrogen-treated ovariectomized female rats, 103Ϯ21 pg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…There is no consensus among investigators as to the possibility of performance impairment of athletes at competitions during the menstrual period. Some authors 45,46 did not find effects from menses on motor performance, while others report that performance improves in the post-menstrual phase and worsens during menses or on the three previous days [37][38][39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Menstrual Dysfunctionmentioning
confidence: 99%
“…Estrogen has many important effects on the cardiovascular, reproductive, and central nervous system as well as for bone maintenance (14). In skeletal muscle, it has been reported that estrogen for example is involved in regulating carbohydrate and lipid metabolism (22). During exercise, estrogen modifies the energetic substrate mobilization improving fat oxidation while sparing muscle glycogen (22).…”
mentioning
confidence: 99%
“…In skeletal muscle, it has been reported that estrogen for example is involved in regulating carbohydrate and lipid metabolism (22). During exercise, estrogen modifies the energetic substrate mobilization improving fat oxidation while sparing muscle glycogen (22). Previous reports indicate a role of estrogen in muscle growth and strength development (31) but available data are not consistent (13).…”
mentioning
confidence: 99%